Evaluating agricultural weather and climate services in Africa: Evidence, methods, and a learning agenda - Vaughan, Catherine; Hansen, James; Roudier, Philippe; Watkiss, Paul; Carr, Edward R. (Wiley, 2019)
Weather and climate services (WCS) are expected to improve the capacity of Africa's agricultural sector to manage the risks of climate variability and change. Despite this, a lack of evidence prevents a realistic analysis of whether such services are delivering on their potential. This paper reviews 66 studies that have evaluated outcomes and/or impacts of agricultural WCS in Africa, highlighting areas that have received relatively more attention as well as persistent gaps. While the evaluation of WCS outcomes is relatively straightforward, estimates of the number of people who access and use these services are uneven (covering a small number of communities in 23 of 54 African countries) and highly variable (with access estimates ranging from ~2 to 86%, depending on the service and the population). Meanwhile, 22 documents estimate the impact of WCS with respect to yields and/or income. Developed with a variety of methods, these estimates are also wide ranging and illustrate how impact is conditioned on a number of characteristics of the service, the user, and the context in which both operate. The paper uses lessons developed through this review to develop a “learning agenda,” or evidence‐building roadmap, to establish priorities that can guide work to improve the design, delivery, and impact of agricultural WCS in Africa. Priority learning areas include activities that can strengthen the evidence of access, use, and impacts of WCS, along with those that can advance the use and usability of evidence so as to improve the design and targeting of WCS services.